P04 FFRCT: Benefits and limitations. a tertiary centre experience at glenfield hospital/university of hospitals leicester. (7th September 2020) - Elfawal, Sara; Khan, Zaid Hussain; Bajaj, Amrita; Das, Indrajeet; Rao, Praveen; Machin, Ruth; Deshpande, Aparna
Abstract : Introduction: FFRCT is a novel software for analysis of CT coronary angiographic images and aims to identify flow limiting disease non-invasively. FFRCT was introduced in our regular practice at 'UHL' in April 2018. This audit sought to assess the utility of FFRCT in evaluating the functional significance of all potentially flow limiting stenosis as seen on conventional CT. Methods: We reviewed all cases which were sent for FFRCT analyses from April 2018 to December 2019. Patients with FFRCT values of >0.80 and <0.80 were identified. In addition, the downstream investigation and management was recorded from the hospital electronic system. Results: A total of 222 cases were sent for FFRCT analysis to Heartflow. FFRCT was <0.80 in 112 patients and > 0.80 in 100 patients in at least one coronary vessel. Invasive angiogram was performed in 59 of these patients, of which 50 had CTFFR< 0.80 and 9 had CTFFR >0.80. Of these, 35 patients had stents or were referred to surgery. Five of the patients that had revascularisation, had a CT FFR of >0.8. Conclusion: We found that FFRCT has a valuable role in assessing the significance of moderate to severe stenosis on CTCA. Interpretation of FFRCT results needs to be made with caution and in conjunction with the CT angiographic images, as the quality of CT images may impact the accuracy of CT FFR values.